2019
DOI: 10.13031/aea.13443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stationary and Moving Infrared Thermometer Measurements Aboard a Center Pivot

Abstract: HighlightsStationary and moving infrared thermometers aboard a center pivot were compared.Comparisons were in terms of directional brightness temperature discrepancies.Discrepancies were within 1.8°C, and many were within 1.0°C.Larger discrepancies tended to occur for sparser vegetation cover.Abstract. Infrared thermometers (IRTs) can measure canopy temperature, which is useful for irrigation and crop management. Center pivot and lateral move irrigation systems are suitable platforms to transport IRTs across c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Using a calibrated black body in a temperature-controlled environmental chamber, tests done after field deployment showed this system to remain accurate after field deployment (Colaizzi et al, 2018) and thus reusable over multiple years, a result borne out by later experience. The system was demonstrated to be effective and accurate both when mounted in fixed positions in the field and when mounted on a moving center pivot lateral with minimal error due to sensor motion (Colaizzi et al, 2019). Dynamax sells the SapIP-IRT in wireless and cabled (SDI-12) versions nationally and internationally.…”
Section: Canopy and Leaf Temperature Sensingmentioning
confidence: 99%
“…Using a calibrated black body in a temperature-controlled environmental chamber, tests done after field deployment showed this system to remain accurate after field deployment (Colaizzi et al, 2018) and thus reusable over multiple years, a result borne out by later experience. The system was demonstrated to be effective and accurate both when mounted in fixed positions in the field and when mounted on a moving center pivot lateral with minimal error due to sensor motion (Colaizzi et al, 2019). Dynamax sells the SapIP-IRT in wireless and cabled (SDI-12) versions nationally and internationally.…”
Section: Canopy and Leaf Temperature Sensingmentioning
confidence: 99%
“…Site-specific VRI was identified as an important emerging topic in the U.S. in the 2017 CP technology brainstorming retreat discussed earlier (table 1), and the consensus was that hardware development has often outpaced the development of management information. Special Collection articles addressing site-specific VRI for CP systems and associated sensors for monitoring and/or control are provided by Colaizzi et al (2019), O'Shaughnessy et al (2019a, and Stone et al (2019).…”
Section: Site-specific Variable-rate Irrigation and Associated Sensormentioning
confidence: 99%
“…Inherent to successful VRI application is the ability to monitor crop status in real-time or near real-time to allow dynamic updating of prescriptive irrigation schemes. In a Special Collection article by Colaizzi et al (2019), a comparison of stationary and moving (i.e., onboard CP) infrared thermometer (IRT) measurements is discussed. The authors found that temperature measurement errors and noise were generally similar between moving and stationary platforms and that addition of more expensive hardware to decrease errors due to CP movement does not appear justified.…”
Section: Site-specific Variable-rate Irrigation and Associated Sensormentioning
confidence: 99%
See 1 more Smart Citation